2010
DOI: 10.29309/tpmj/2010.17.04.2978
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Thyroid Nodule

Abstract: Objectives: To determine frequency of malignancy in solitary thyroid nodule. Design: Case-series study. Place and Duration of Study: The study was conducted at Department of Surgery, Combined Military Hospital Rawalpindi, from April 2002 till April 2003. Patients and Methods: Sixty patients with clinical solitary thyroid nodule fulfilled the selection criteria and were included in the study. Thyroid function tests, ultrasonography and thyroid scanning was done. Finally FNAC and histopathology were done in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…19 Other study done by Tarrar AM et al showed that 13.33% of solitary thyroid nodules were found to have malignant lesions and 86.67% were benign and papillary carcinoma was most common malignancy found in his study. 20…”
Section: Table III Fnac Diagnosis Of Thyroid Swelling (N=80)mentioning
confidence: 99%
“…19 Other study done by Tarrar AM et al showed that 13.33% of solitary thyroid nodules were found to have malignant lesions and 86.67% were benign and papillary carcinoma was most common malignancy found in his study. 20…”
Section: Table III Fnac Diagnosis Of Thyroid Swelling (N=80)mentioning
confidence: 99%